Genetic Diversity and Population Structure of Acanthopagrus latus in the South China Sea - Cheng-He Sun; Qun Zhang; Chang-Hu Lu (Animals)
The yellowfin seabream Acanthopagrus latus (Houttuyn, 1782) belongs to the order Spariformes and family Sparidae and is tender, rich in fat, and nutritious, making it a high-value seafood variety along the China coast. The fry can be used for large-scale aquaculture in both seawater and freshwater. Due to environmental pollution and excessive fishing, natural A. latus populations have declined significantly in recent years, which severely depletes genetic diversity. Here, we analyzed the genetic structure of four wild A. latus populations in the South China Sea to provide insights into the genetic resources. In particular, we analyzed 40 samples from four sampling sites through whole-genome resequencing, yielding 515 Gb of raw data and 132,505,081 single nucleotide polymorphisms. Population structure, phylogenetic, and principal component analyses revealed that the four populations were homogeneous and did not show clustering based on geographical origin, indicating extensive admixture. This could be attributed to recent enhancement and release activities in the South China Sea. This information may help to protect and utilize A. latus germplasm resources.